Analisis Service Quality terhadap Kepuasan Pelanggan pada PDAM Kota Surabaya - Sudapet, Nyoman (BISMA (Bisnis dan Manajemen), 2018)
Objective of this research is to analysis the affect of responsiveness, assurance, tangible, empathy and reliability due to Surabaya PDAM consumer's satisfaction. The sample observed was all of the Surabaya PDAM customers at about 60 respondents, with simple random sampling. Measurement device used to measure service quality is gap analysts, multiple regression, T-test, F-test, determination coefficients, normality test, multicoliniarity test and heterokedastisity test. Based on gap analysis results, the dimension of responsiveness and empathy are having a positive gap, means that the service quality of Surabaya PDAM is already meet the customers satisfaction, but in the insurance, tangible and reliability are having negative gap, means that customers hope due to the service of Surabaya PDAM is higher than service accepted by the customers, from the quality service dimension regression test that is responsiveness, assurance, tangible, empathy, and reliability are having positive significant effect on customer satisfaction of Surabaya PDAM showed that hypothesis with the biggest affection is responsiveness variable, then empathy, tangible, assurance, and reliability, from T-test it was obtained responsiveness variables, empathy with significant number at 1% and assurance, tangible, reliability, are significant at 5%, fount = 19.140 with confidential interval 99% or n= 0,01 by entering service quality variable, this model is fit. Determination coefficient number showed 63,9% customer satisfaction variable variation can be explained by the variable from service quality dimension. Classical assumption test showed that data range is normal and do not showed multicolinearity and heterokedastisity test